A RELAÇÃO DA DIÁSTASE ABDOMINAL GESTACIONAL COM ALTERAÇÕES POSTURAIS NA GRAVIDEZ - DREHER, DANIELA Z.; BITTENCOURT, DARLENE C. D.; LIMA, CAROLINE H. L. D.; WOHLENBERG, CHEILA (Salão do Conhecimento, 2013)
Resumo